2018
DOI: 10.3389/fnsys.2018.00027
|View full text |Cite
|
Sign up to set email alerts
|

Pain Input After Spinal Cord Injury (SCI) Undermines Long-Term Recovery and Engages Signal Pathways That Promote Cell Death

Abstract: Pain (nociceptive) input caudal to a spinal contusion injury increases tissue loss and impairs long-term recovery. It was hypothesized that noxious stimulation has this effect because it engages unmyelinated pain (C) fibers that produce a state of over-excitation in central pathways. The present article explored this issue by assessing the effect of capsaicin, which activates C-fibers that express the transient receptor potential vanilloid receptor-1 (TRPV1). Rats received a lower thoracic (T11) contusion inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 55 publications
1
27
1
Order By: Relevance
“…Peripheral application of the irritant capsaicin 24 h after a spinal contusion injury engages an acute up-regulation of signal pathways associated with cell death and impairs long-term recovery (Turtle et al, 2018). The present experiment examines whether this treatment also promotes hemorrhage after injury and how this effect varies over time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Peripheral application of the irritant capsaicin 24 h after a spinal contusion injury engages an acute up-regulation of signal pathways associated with cell death and impairs long-term recovery (Turtle et al, 2018). The present experiment examines whether this treatment also promotes hemorrhage after injury and how this effect varies over time.…”
Section: Resultsmentioning
confidence: 99%
“…Elsewhere, we have shown that noxious stimulation can activate signal pathways linked to neural over-excitation and cell death (e.g., caspase 1, 3 and 8) (Ferguson et al, 2008; Garraway et al, 2014; Huie et al, 2015; Turtle et al, 2018). These processes could also contribute to the breakdown of the BSCB by initiating cell death within endothelial cells or indirectly by depleting energy stores (ATP).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations